Acute Pancreatitis in Henoch-Schonlein Purpura Complicated by Large Pseudocyst Formation Requiring Cystogastrotomy (Indian Journal of Case Reports, 2021)
Henoch-Schönlein purpura (HSP) is a small-vessel vasculitis that typically occurs in children and causes characteristic purpuric skin lesions occasionally associated with multisystemic involvement. Gastrointestinal symptoms appear in 70% of the patients varying from mild to severe abdominal pain resembling an acute abdomen but HSP rarely presents with acute pancreatitis. Here, we report the case of an 11-year-old girl admitted with HSP-associated recurrent episodes of acute pancreatitis complicated with large pseudocyst formation. She was treated with pulse methylprednisolone followed by oral prednisolone and a single cyclophosphamide pulse but finally required a cystogastrotomy.